Microsoft Dynamics 365 AI for Business Insights. - Dmitry Shargorodsky; PACKT (GB: Packt, 2024)
Streamline your business operations by leveraging AI across key functions using practical examples and insightful case studies Key Features Uncover the practical applications of Dynamics 365 AI across sales, customer service, marketing, and finance Explore Dynamics 365's integration with advanced AI tools such as OpenAI, Azure Open AI, and MS Copilot Learn from real-world examples and case studies Purchase of the print or Kindle book includes a free PDF eBook Book Description If there is one hot topic being discussed in every boardroom meeting today, it's AI. With Microsoft Dynamics 365 AI proving to be a game-changer, it's essential for business professionals to master this tool. Microsoft Dynamics 365 AI for Business Insights will help you harness AI across key business functions to streamline processes and enhance customer experiences. Written by a seasoned professional with 15+ years of experience, this book guides you through Dynamics 365 AI's practical applications across sales, customer service, marketing, and finance departments. You'll learn how to enhance customer experiences, streamline sales processes, optimize marketing strategies, and improve financial forecasting. This book also explores the integration of generative AI tools such as OpenAI Service, Azure Open AI, language models, and Microsoft Copilot within the Dynamics 365 ecosystem. With real-world examples, case studies, and expert insights, you'll discover the transformative potential of this powerful toolkit. As well as driving sales insights and implementing fraud protection, you'll explore emerging AI trends, Microsoft's roadmap for Dynamics 365 AI, and the upcoming features. By the end, you'll be all set to unlock new growth opportunities using Dynamics 365 AI. What you will learn Overcome common challenges in Dynamics 365 AI implementation with ease Delve into the practical applications of advanced generative AI tools Integrate cutting-edge tools such as OpenAI Service, Azure Open AI, language models, and Microsoft Copilot with Dynamics 365 AI Derive insights from real-world examples of successful AI implementation Discover best practices and strategies for leveraging AI to find useful business insights and enhance operations Explore Microsoft's roadmap for Dynamics 365 AI and the forthcoming trends in AI for business Who this book is for This book is for Dynamics 365 consultants, architects, and IT managers, willing to implement AI in their organizations. Business consultants advising on business technology, especially those focused on Microsoft Dynamics 365, will find it useful for enhancing their skills. A basic understanding of Microsoft Dynamics 365 and its suite of business applications will be beneficial as the book's focus is on implementing the tool's AI modules. Familiarity with the principles of artificial intelligence and how it is applied in a business context will also be helpful.
Data in extended ASCII character set.
Mode of access: Internet.